(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This article is the result of a research carried out during the doctoral thesis Diálogos entre arte y moda en la actualidad presented in March 2015 at the Faculty of Fine Arts of the University of Vigo in Spain. In the panorama of contemporary creation, the confluence between art and fashion generates a feedback and hybridisation process by historically delimited and autonomous fields. To understand this dynamic, a comparison was made between the artist Cindy Sherman and the fashion designer Miuccia Prada based on an individual analysis of both their creative process and the result of their production. To establish the body as a form of expression and clothing as a proposal, characteristics that provide the lines of connection between art and fashion, allow to observe recurrent elements from the creation process until the result of the proposals that corroborate the confluence between the creators and their respective fields.